Implementasi Pasal 74 Undang – Undang Perseroan Terbatas (PT) Nomor 40 Tahun 2007 Tentang Corporate Social Responsibility (CSR) Sebagai Modal Sosial - Hasan Asya'ri (Fakultas Hukum Universitas Mataram, 2015)
Corporate Social Responsibility (CSR) is one of the obligations that must be implemented by the company in accordance with the contents of article 74 of Law - Corporate Law (Company Law) the latest, Law. No. 40 of 2007. This study aims to analyze and assess how PT. State Electricity Company NTB do CSR. In addition, through this research will also be identified in about constraints - the constraints faced by PT. State Electricity Company NTB in implementing CSR. This study used juridical - normative and juridical - empirical, that is by doing an inventory of domestic law and related to corporate social responsibility in relation to the alleviation of problems - social problems, obtain explanations and know - things about corporate social responsibility, and the constraints faced. From the results it can be concluded in the implementation of social responsibility, PT PLN doing activities - activities as follows: Community Relations, this activity involves the development of understanding through communication and information to the relevant parties. Community Services, program assistance in these activities related to public service or public interest. Community Empowering, this activity consists of programs that provide wider access to the public to support their independence. Nature Conservation, environmental development program implemented in the form of educational assistance for community activities around the location of transmission and distribution are not capable, but has great intelligence and willingness to continue their education. Additionally, conducted through nature conservation activities such as participation greening program organized by external parties to cooperate with the Government and the realization of the greening around PLN installation. In the implementation of CSR, PT PLN encountered obstacles - obstacles as follows: The main challenge faced by PT PLN any public mistrust and misperceptions that arise from the surrounding community PLN installation. PT PLN unable to maximize service due to power shortage.